Synergism between Inositol Polyphosphates and TOR Kinase Signaling in Nutrient Sensing, Growth Control, and Lipid Metabolism in Chlamydomonas. Issue 9 (6th September 2016) - Couso, Inmaculada; Evans, Bradley S.; Li, Jia; Liu, Yu; Ma, Fangfang; Diamond, Spencer; Allen, Doug K.; Umen, James G.
Abstract : A mutation in a Chlamydomonas inositol kinase sensitizes cells to inhibition of TOR kinase signaling in a carbon source-dependent manner and uncouples lipid accumulation from starvation signals. Abstract: The networks that govern carbon metabolism and control intracellular carbon partitioning in photosynthetic cells are poorly understood. Target of Rapamycin (TOR) kinase is a conserved growth regulator that integrates nutrient signals and modulates cell growth in eukaryotes, though the TOR signaling pathway in plants and algae has yet to be completely elucidated. We screened the unicellular green alga Chlamydomonas reinhardtii using insertional mutagenesis to find mutants that conferred hypersensitivity to the TOR inhibitor rapamycin. We characterized one mutant, vip1-1, that is predicted to encode a conserved inositol hexakisphosphate kinase from the VIP family that pyrophosphorylates phytic acid (InsP6 ) to produce the low abundance signaling molecules InsP7 and InsP8 . Unexpectedly, the rapamycin hypersensitive growth arrest of vip1-1 cells was dependent on the presence of external acetate, which normally has a growth-stimulatory effect on Chlamydomonas. vip1-1 mutants also constitutively overaccumulated triacylglycerols (TAGs) in a manner that was synergistic with other TAG inducing stimuli such as starvation. vip1-1 cells had reduced InsP7 and InsP8, both of which are dynamically modulated in wild-type cells by TOR kinase activity and the presence of acetate. Our data uncover an interaction between the TOR kinase and inositol polyphosphate signaling systems that we propose governs carbon metabolism and intracellular pathways that lead to storage lipid accumulation.